Numerical Analysis of the Mixed 4th-Order Runge-Kutta Scheme of Conditional Nonlinear Optimal Perturbation Approach for the EI Niño-Southern Oscillation Model (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, we propose and analyze the mixed 4th-order Runge-Kuttascheme of conditional nonlinear perturbation (CNOP) approach for the EI Niño-SouthernOscillation (ENSO) model. This method consists of solving the ENSO modelby using the mixed 4th-order Runge-Kutta method. Convergence, the local and globaltruncation error of this mixed 4th-order Runge-Kutta method are proved. Furthermore,optimal control problem is developed and the gradient of the cost function isdetermined.